2019
DOI: 10.1111/eth.12923
|View full text |Cite
|
Sign up to set email alerts
|

Giraffe (Giraffa camelopardalis) social networks in areas of contrasting human activity and lion density

Abstract: The adaptive value of close social bonds and social networks has been demonstrated in a variety of vertebrate taxa. While the effect of predators on populations is well established, disturbance by humans is increasingly being identified as affecting the behaviour and reproductive success of animals and can have significant impacts on their survival. We used a concurrent analysis of two adjacent giraffe Giraffa camelopardalis populations in Kenya to determine whether human activities and high predation affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 131 publications
(215 reference statements)
1
16
0
Order By: Relevance
“…Hyenas living in areas of a national park with higher levels of human activity had less dense social networks, indicating animals interacted less with other clan members (Belton et al., 2018). Giraffes in a population with high levels of tourism and a high density of lions appeared to have weaker associations and more exclusive relationships than in a population without lions and few tourists (Muller et al., 2019). The results of that study, while remaining unclear due to a lack of statistical support, do align with our theory‐driven prediction, and our statistically significant findings, that disturbances can disrupt social structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hyenas living in areas of a national park with higher levels of human activity had less dense social networks, indicating animals interacted less with other clan members (Belton et al., 2018). Giraffes in a population with high levels of tourism and a high density of lions appeared to have weaker associations and more exclusive relationships than in a population without lions and few tourists (Muller et al., 2019). The results of that study, while remaining unclear due to a lack of statistical support, do align with our theory‐driven prediction, and our statistically significant findings, that disturbances can disrupt social structure.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption to social systems also may be a contributing factor in population declines, but, to date, anthropogenic effects on social structure of giraffes remain unclear. One recent study by Muller, Cuthill, and Harris (2019) reported differences in network metrics across two separated, small, enclosed populations of Rothschild's giraffes in Kenya.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our focus was on improving the understanding of elephant social behavior in areas where poaching is an ongoing threat, our work may be of use to translocation practitioners working with other vulnerable species (Mengak, 2018; Muller et al, 2019). In the past, translocation specialists put their efforts into the optimization of the demographic (Miller et al, 1999) and genetic (Weeks et al, 2011) properties of target populations, as well as attributes of habitats intended for translocation (McCoy et al, 2014).…”
Section: Discussionmentioning
confidence: 99%